Business Model Canvas : Smart Compose Machine / Fatin Nur Azreena Mohd Fauzi - Mohd Fauzi, Fatin Nur Azreena (2020)
In New Product Development, I had built a product that could turn residual foods or food waste into nutrient soil amendments. This machine is called "Smart Compose Machine". The Business Model Canvas is a conceptual tool for explaining the different elements of how an organization operates. It shows what my business is doing, for and with whom, the tools it needs to do that, and how money moves within and outside this business. This can be used when constructing new models or when evaluating existing models.